2008
DOI: 10.1091/mbc.e07-05-0515
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Mitochondria in Presynaptic Development at the Neuromuscular Junction

Abstract: Mitochondria with high membrane potential (⌬⌿ m ) are enriched in the presynaptic nerve terminal at vertebrate neuromuscular junctions, but the exact function of these localized synaptic mitochondria remains unclear. Here, we investigated the correlation between mitochondrial ⌬⌿ m and the development of synaptic specializations. Using mitochondrial ⌬⌿ m -sensitive probe JC-1, we found that ⌬⌿ m in Xenopus spinal neurons could be reversibly elevated by creatine and suppressed by FCCP. Along naïve neurites, pree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 50 publications
3
80
0
2
Order By: Relevance
“…It has been shown that an increased ⌬ m enhances the rate of mitochondrial transport, most obviously retrograde movement (40). We found that CXCL12 increased ⌬ m , but no significant differences were observed between the responses of control and Miro-1-silenced T cells (see Fig.…”
Section: Resultsmentioning
confidence: 52%
“…It has been shown that an increased ⌬ m enhances the rate of mitochondrial transport, most obviously retrograde movement (40). We found that CXCL12 increased ⌬ m , but no significant differences were observed between the responses of control and Miro-1-silenced T cells (see Fig.…”
Section: Resultsmentioning
confidence: 52%
“…To test this, a second neurodegenerative stimulus, carbonyl cyanide-ptrifluoro-methoxy phenylhydrazone (FCCP), an uncoupling reagent disrupting mitochondrial function, was used (33). In control neurons, FCCP reduced mitochondrial size (Fig.…”
Section: Srf Deficiency Modulates Mitochondrial Morphology and Distrimentioning
confidence: 99%
“…These include the allocation of energy in the form of ATP through the activity of the respiratory chain, the regulation of the levels of second messengers such as calcium and reactive oxygen species (ROS), the synthesis of lipids and other metabolites, and the integration of pro- and anti-apoptotic signals. Energy demand is mainly driven by the neuronal requirement for energy to maintain activities such as axonal transport (1), synaptic transmission (release and recycling of neurotransmitters) (2), ion channel and ion pump activity (3), and assembly of the actin cytoskeleton among synapses [138,139,140] (4). Moreover, the maintenance of calcium homeostasis that is critical for neuronal synaptic function is controlled by mitochondria at the synapse [141] (5).…”
Section: Axonal Transport Of Mitochondria and Their Componentsmentioning
confidence: 99%